(untitled) (Journal of Medical & Health Sciences Review, 2025)
The progression from insulin resistance to overt Type 2 Diabetes Mellitus (T2DM) is defined by the failure of pancreatic β-cells to compensate. While functional deficits are well-studied, comprehensive analysis of the concomitant structural alterations in pancreatic islets is crucial. This study aimed to perform a quantitative histomorphological assessment of pancreatic islets in a diet-induced murine model of T2DM to correlate structural changes with metabolic phenotype. The study conducted at Dr. Ruth K. M. Pfau, Civil Hospital Karachi where Twenty-four C57BL/6J male mice were allocated into two groups: a control group fed a normal chow diet (NCD, n=12) and an experimental group fed a high-fat diet (HFD, 45% kcal from fat, n=12) for 12 weeks. Metabolic profiling included weekly body weight, fasting blood glucose, and an intraperitoneal glucose tolerance test (IPGTT). Pancreatic tissues were processed for histology (H&E) and immunohistochemistry (anti-insulin, anti-glucagon). Morphometric analysis quantified islet density, individual islet area, β-cell area, and β-cell mass. HFD-fed mice developed significant obesity, hyperglycemia, and glucose intolerance (p < 0.01). Morphometrically, HFD islets exhibited a 52% increase in average islet area (p < 0.001) and a 92% increase in β-cell mass (p < 0.001) compared to NCD controls, indicating compensatory hypertrophy. However, HFD islets displayed significant pathological alterations, including loss of architectural integrity, cytoplasmic vacuolation, and pyknotic nuclei. The size distribution of islets was heterogeneous in the HFD group, showing a bimodal pattern of both hypertrophied and atrophied islets. The HFD model induces a state of metabolic stress that triggers significant but pathological remodeling of pancreatic islets. The coexistence of compensatory hypertrophy with clear signs of cellular degeneration illustrates the structural paradox of T2DM—a system struggling to adapt while simultaneously undergoing failure. These findings underscore that the decline in β-cell function is intrinsically linked to a decline in structural integrity.